Feeding/Eating Problems in Children Who Refrained From Treatment in the Past: Who Did (Not) Recover? - Dumont, Eric; Jansen, Anita; Duker, Pieter C.; Seys, Daniel M.; Broers, Nick J.; Mulkens, Sandra (Frontiers in Pediatrics, 2022)
Background: Young children with disordered feeding may be at increased risk for a prob-lematic eating future. This retrospective study attempts to identify predictors of later feed-ing problems. Objectives: Children (N=236) with disordered feeding, who refrained from behavioral treatment after consultation at a tertiary treatment center for feeding and eating problems were followed-up after, on average, 6 years and 3 months (timepoint 2). Method: Logistic regressions were carried out with characteristics taken at intake (timepoint 1) - sex, pre/dysmaturity, gastro-intestinal disease, history of age-adequate feed-ing, syndrome/developmental impairment, autism spectrum disorder, comorbidity, age, and several variables of a restrictive- and selective food intake – and duration between timepoint 1 and 2, as predictor variables, and age-appropriate food intake at t2 as the dependent varia-ble. Results: Despite improvement over time, 63% did not reach an age-adequate food intake at t2. Predictors of age-inadequate food intake were: (a) older age; (b) sex (male), (c) longer duration between timepoint 1 and timepoint 2; (d) autism spectrum disorder; (e) selective texture choices and (f) lack of varied nutritional intake. Conclusion: This study shows that most untreated young children’s feeding problems do not improve over years. Besides the advice to seek help at an early age, it seems especially rec-ommended to treat (male) children with autism spectrum disorder and selective feeding pat-terns.